Laccase immobilized on amino-functionalized magnetic Fe3O4-SiO2 core–shell material for 2, 4-dichlorophenol removal. Issue 17 (29th July 2022) - Ren, Dajun; Jiang, Shan; Fu, Linjun; Wang, Zhaobo; Zhang, Shuqin; Zhang, Xiaoqing; Gong, Xiangyi; Chen, Wangsheng
ABSTRACT: In this study, an amino-functionalized magnetic silica microsphere material (Fe3 O4 -SiO2 -NH2 ) was prepared. Using glutaraldehyde as a cross-linking agent, Trametes versicolor laccase was adsorbed-covalently bonded and immobilized on the material to prepare Laccase @ Fe3 O4 -SiO2 . In addition, the materials were characterized and analysed by SEM, TEM, XRD, FT-IR and VSM. Finally, the thermal inactivation dynamics of immobilized laccase in polar/non-polar/toxic systems and the adsorption and degradation of 2, 4-DCP were studied. The results showed that Laccase @ Fe3 O4 -SiO2 under the optimal conditions (pH 6, temperature 65°C, initial concentration of 2, 4-DCP 10 mg/L), the removal rate was as high as 81.6%. Moreover, compared with free laccase, immobilized laccase had good tolerance under low pH and high-temperature conditions, and storage stability was also greatly improved. After repeated use for 7 times, Laccase @ Fe3 O4 -SiO2 can still maintain 59% removal rate of 2, 4-DCP, which gives it the potential for industrial applications. GRAPHICAL ABSTRACT: UF0001